Mucormycosis in Hematologic Malignancies: Clinical Follow-Up and Treatment Results - Nagehan Didem Sarı; Istemi Serin; Tolga Kırgezen; Mehmet Hilmi Doğu (İstanbul Medical Journal, 2021)

(untitled)
Introduction:Mucormycosis is an aggressive-progressive invasive fungal infection caused by mold fungi in the division of mucorales of the zygomycetes class with high mortality, and is the most common fungal infection in patients with hematologic malignancies.Methods:This study retrospectively evaluated patients with mucormycosis diagnosis between January 2015 and December 2019, including demographic features, hematologic diseases and comorbidities, radiological evaluations, symptoms and signs, treatments, and outcomes.Results:Maxillofacial 9/19 (47.37%) of patients and 10/19 (59.9%) rhinoorbital mucor. Hematologic malignancy was observed in 15 (78.95%) patients, whereas others had additional pre-disposing factors, such as diabetes mellitus and chronic renal failure. The most common find-ings were persistent fever, mucopurulent nasal flux, and periorbital edema. Endoscopic sinus surgery + medication was administered in 12/19 (62.2%) patients and antifungal therapy in 7/19 (37.8%). In addition, 15/19 (79.95%) patients died and 4/19 recovered with sequela.Conclusion:The first large-scale mucormycosis study from our country will guide in determining the treatment algorithm. Effective and early surgery and antifungal application reduce mortality in mucormycosis by early diagnosis and multidisciplinary approach, without bone destruction in the paranasal sinus computed tomography with recurrent fever and earlystage sinusitis finding by performing a biopsy.